Agile Governance in The Healthcare Sector Through The Kurma Manis Program in The City of Pekanbaru - Novia Gardini; Febri Yuliani; Nur Laila Meilani; Zulkarnaini Zulkarnaini (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study aims to analyze the implementation of Agile Governance in the healthcare sector through the Kurma Manis (Healthy Community Home Visits) Program in Pekanbaru City. Agile Governance is an adaptive, collaborative, and responsive governance approach that is highly relevant in the dynamic healthcare service system. The Kurma Manis Program is a healthcare innovation that involves direct home visits to deliver preventive and promotive services. This research uses a descriptive qualitative approach with data collection techniques including in-depth interviews, observation, and documentation. The results indicate that Agile Governance principles such as cross-sector collaboration, rapid feedback, and continuous improvement have been effectively implemented in the program. However, several challenges remain, particularly in stakeholder coordination and limited human resources. The study concludes that the application of Agile Governance in the Kurma Manis Program enhances the effectiveness of public healthcare services in Pekanbaru City.